The Relationship Of Hiv/Aids Events With Injecting Drug Use - Deviana Farhani; Indah Laily Hilmi (Sean Institute, 2022)
HIV stands for Human Immunodeficiency Virus infection and AIDS stands for Acquired Immunodeficiency Syndrome. HIV and AIDS cannot be separated because AIDS is a disease caused by the HIV virus. The HIV virus will attack the human immune system, more specifically attacking helper T cells, this will cause a decrease in the immune system of infected individuals. The risk of spreading HIV/AIDS infection occurs more through unsafe sex than through drug use. There are so many negative impacts obtained by ODHA both from the outside environment and from within themselves